Africa-Wide Capacity-Building Workshop on Strengthening Rice Seed Networks - NDindeng, S.A.; Bah, S.; Willem, J.; van Casteren, A.; Tang, E.; Ndung’u, J.; Kittika, M.; Wakilongo, N.J. (AfricaRice, 2025)
The Africa-Wide Capacity-Building Workshop on Strengthening Rice Seed Networks was held from 25–27 August 2025 in M’bé, Côte d’Ivoire, hosted by AfricaRice and its partners. The event brought together 123 stakeholders from 18 countries, including NARES, seed enterprises, millers, regulators, meteorological agencies, farmer organizations, and agricultural digital solution providers. The workshop was convened against the backdrop of Africa’s persistent rice seed challenges, including weak seed systems, poor traceability, circulation of counterfeit seeds, and limited access to climate-smart varieties. Through presentations, case studies, and breakout sessions, participants examined approaches to strengthen national and regional seed networks, integrate agricultural digital platforms such as eProd for traceability and data-driven monitoring, and embed climate services and early warning systems into seed planning. Case studies from Ghana, Uganda, Nigeria, Egypt, Mali, Burkina Faso, Senegal, and Côte d’Ivoire highlighted diverse governance models, best practices, and systemic weaknesses such as poor institutionalization, corruption risks, and rigid governance structures. Deliberations led to several important agreements. Each country committed to establishing or strengthening a national seed network secretariat, with interim officials nominated where none exist. NARES partners were tasked with leading seed data collection covering demand, varieties, seed classes, and enterprises using retrospective data from 2021 onward. All seed enterprises will be onboarded onto the eProd platform, enabling real-time tracking of seed production, farmer demographics, acreage, and varieties, with AfricaRice providing technical backstopping. Furthermore, stakeholders agreed on the importance of inclusive partnerships that bring together meteorological departments, financial institutions, NGOs, millers, seed enterprises and farmer groups to improve climate resilience, facilitate market access, and build farmer trust in certified seeds.The workshop outcomes align closely with AfricaRice’s RSD flagship projects RIZAO, Reverse Linkage, TAAT II, and REWARD all of which emphasize varietal scaling, digital innovations, climate-smart solutions, and youth empowerment. Collectively, the workshop reinforced the urgency of building resilient, transparent, and inclusive seed systems anchored in strong governance, robust partnerships, and digital integration to drive productivity and safeguard Africa’s food security.